The effect of nuciferine on the renal dysfunction following ischemia-reperfusion injury - Sundus M. Sallabi; Loay Lubbad; Harun R. Toumi; Waheed F. Hammad; Manjusha Sudhadevi; Jasmine Abdul Rasheed; Awwab F. Hammad; Mustafa M. Ardah; Suhail Al-Salam; Fayez T. Hammad (PLoS ONE, 2025)
Renal ischemia-reperfusion injury (IRI) is an inevitable consequence of several clinical conditions and surgical procedures including renal transplantation and resuscitation following systemic hypotension. It leads to immediate renal dysfunction and might result in long-term renal damage. Therefore, there is an ongoing effort to mitigate the deleterious effects of the IRI on the kidney. Recently, there has been a recent interest in using natural compounds as alternative remedies in many diseases. Thus, the aim of this research was to study the effect of nuciferine, a phytochemical compound extracted from the plant Nelumbo nucifera Gaertn, on the renal dysfunction in a rat mode of IRI. Nuciferine was administered orally as single daily dose of 30 mg/kg for 9 days prior to IRI and continued for 3 days post-IRI. G-Sham (n = 11) underwent sham surgery whereas G-IRI (n = 12) and G-IRI/NF (n = 12) underwent bilateral warm renal ischemia for 35 minutes. G-IRI/NF received nuciferine. Renal functions and histological changes were assessed before starting the medication, just prior to IRI and 3 days after IRI. Nuciferine significantly attenuated the alterations in serum creatinine, serum urea, creatinine clearance and urinary albumin creatinine ratio. This was associated with significant attenuation of the alterations in renal injury markers, several cytokines including pro-inflammatory, pro-fibrotic and apoptotic cytokines and in histological changes. In conclusion, nuciferine has reno-protective effects on the IRI-induced renal dysfunction. These findings might be of clinical significance.